Simple Additive Weighting Untuk Penentuan Target Pasar - Gabriel Alan Wijaya; Marfuah Marfuah; Suryo Widiantoro (LPPM STIKI MALANG, 2023)
Changes in information and communication technology have encouraged the formation of an information society. One of the strategic elements for business organizations is processing data quickly and accurately for decision making. Therefore we need a computer-based decision support system that can support the company's decision-making process quickly and accurately. Currently, Glints Talenthub Batam still uses manual methods for decision making in determining the target market, so it takes a long time and results are less accurate. Based on this, the authors try to develop a computer-based decision support system with the Simple Additive Weighting (SAW) method to assist the decision-making process in determining the target market at Glints Talenthub Batam. The results of this study are useful for getting a faster and more accurate decision on which target market to take at Glints Talenthub Batam. In this case, the best target market decision to make is Canada and the United States (San Francisco) ranking first with a final score of 18.68, followed by the United Kingdom in the next rank with a final score of 18.35.